How Professor Oswald Balzer Accidently Helped Hungarians to Legalize the Annexation of the White Water Valle - Matuszewski, Jacek (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
In 1769, Austria had annexed by force the lands of the Polish starosty of Nowy Targ to Hungary, including the White Water Valley. In 1772 the Empress took back these territories from Hungary and attached them to Austria. The conflict over the Austro-Hungarian border in the Tatra Mountains, lasting throughout the nineteenth century, was settled in 1902 by an arbitration award. The Tribunal approved almost all of Austria’s demands, but at the same time it submitted to the stubborn demands of the Austrian defense attorney prof. Oswald Balzer, and decided to deprive Galicia of the right to regain the White Waters Valley, which had been forcibly seized by the Hungarians.